Preventive Guidelines for Disinfection and Microbiological Processes During Handling of COVID-19 Samples - Roman, Muhammad; Saleem, Sidra; Jahan, Shah; Ul Haq, Faiz; Hayat, Husnul; Waheed, Abdul; Masood, Nadeem (Europasian Journal of Medical Sciences, 2020)
Since the first detection and emergence of SARS-CoV-2 in Wuhan, China in December 2019, it has become a worldwide health concern. Human to human airborne transmission and persistence of SARS-CoV-2 on inanimate surfaces or contaminated hands have been documented. Droplets transmission has been recognized as a major source of virus spread. Most of the samples received in the pathology laboratories were for the diagnosis of the corona virus disease-2019 (COVID-19). The highest concentration of SARS-CoV-2 has been observed in the respiratory specimens compared to the non-respiratory specimens as the virus is present in lower concentration in urine, blood, and stool. The guidelines in this article present the procedures for disinfection and microbiological processes that should minimize the risk of infection to the laboratory personnel. Surface disinfection with sodium hypochlorite (0.1%), ethanol (62%-71%), or hydrogen peroxide (0.5%) with an exposure time of 1 min is likely to be efficient against SARS-CoV-2. However, the ultraviolet light at 254 nm, glutaraldehyde, formalin, heat treatment of 65 ◦C or above, and acidic (pH <3) may be effective for inactivating SARS-CoV-2. The SARS-CoV-2 can remain infectious on the inanimate surfaces for up to 9 days so laboratory personnel should be aware of the need for following the biosafety protocols while processing the specimens.